2019
DOI: 10.18235/0002014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Public Investment: The Impact of MapaRegalías in Colombia

Abstract: the cost incurred by public officials and citizens when monitoring the use of royalties. The main finding is that after the release of Mapa-Regalías, public investment projects financed with royalties showed an average increase in efficiency of execution of 7.996 percentage points.T his paper analyzes the impact of Mapa-Regalías on efficiency in the execution of public investment projects in Colombia. MapaRegalías is an online platform that displays geo-referenced information and data on royalties coming from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Three months after the release of InvestmentMap, financial progress of public investment projects uploaded onto the platform increased by 18 percentage points, and physical progress increased by 8 percentage points compared to unpublished projects (Rossi, Vazquez, and Vieyra, 2020). The other study also focused on the use of InvestmentMap finds that after the release of MapaRegalías in Colombia, public investment projects financed with royalties showed an average increase in efficiency of execution of close to 8 percentage points (Lauletta et al, 2019). Both studies are important since they foreshadow the practical importance that InvestmentMap has had in Paraguay, including generating institutional knowledge for technological and information management, and the spillovers that this might have generated in adjacent institutions.…”
Section: Digital Technologies To Improve Transparency and Integrity I...mentioning
confidence: 98%
“…Three months after the release of InvestmentMap, financial progress of public investment projects uploaded onto the platform increased by 18 percentage points, and physical progress increased by 8 percentage points compared to unpublished projects (Rossi, Vazquez, and Vieyra, 2020). The other study also focused on the use of InvestmentMap finds that after the release of MapaRegalías in Colombia, public investment projects financed with royalties showed an average increase in efficiency of execution of close to 8 percentage points (Lauletta et al, 2019). Both studies are important since they foreshadow the practical importance that InvestmentMap has had in Paraguay, including generating institutional knowledge for technological and information management, and the spillovers that this might have generated in adjacent institutions.…”
Section: Digital Technologies To Improve Transparency and Integrity I...mentioning
confidence: 98%
“…For example, Lauletta et al (2019) show that implementation of the MapaRegalías platform in Colombia could increase efficiency in the execution of investment projects. 3 Along the same lines, Rossi, Vazquez, and Cruz (2020) find that the MapaInversiones platform in Costa Rica could improve the performance of investment projects.…”
Section: Transparent Access To Public Information Through Online Plat...mentioning
confidence: 99%
“…Colombia, for example, developed an open data platform to track the use of mining royalties and the infrastructure projects that they finance. A recent evaluation by Lauletta et al (2019) found that the platform increased the efficiency of public investment projects and reduced monitoring costs, both for independent overseers and within the government itself.…”
Section: Leveraging Integrity Analyticsmentioning
confidence: 99%